2006
DOI: 10.1002/ajp.20318
|View full text |Cite
|
Sign up to set email alerts
|

Use of a tool‐set by Pan troglodytes troglodytes to obtain termites (Macrotermes) in the periphery of the Dja Biosphere Reserve, southeast Cameroon

Abstract: At the northern periphery of the Dja Biosphere Reserve (southeastern Cameroon) we recorded a new use of a tool-set by Pan troglodytes troglodytes to prey on Macrotermes muelleri, M. renouxi, M. lilljeborgi, and M. nobilis. We recovered 79 puncturing sticks and 47 fishing probes at 17 termite nests between 2002 and 2005. The mean length of the puncturing sticks (n = 77) and fishing probes (n = 45) was 52 cm and 56 cm, respectively, and the mean diameter was 9 mm and 4.5 mm, respectively. Sixty-eight percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 9 publications
(14 reference statements)
0
27
0
1
Order By: Relevance
“…The implications of the failures reported for Povinelli's chimpanzees (2000) are problematic, relative to findings with other captive nonhuman primates (e.g., Deblauwe et al, 2006;Fragaszy et al, 2004;Sakura and Matsuzawa, 1991;Tonooka et al, 1997;Westergaard et al, 1995;Yocom and Boysen, 2010), but especially given the demonstrated prowess of wild chimpanzees in extensive and creative use of objects as tools in their environment. Why would captive chimpanzees not exhibit knowledge of physical support when such capabilities are both advantageous and necessary for their survival in the wild?…”
mentioning
confidence: 84%
“…The implications of the failures reported for Povinelli's chimpanzees (2000) are problematic, relative to findings with other captive nonhuman primates (e.g., Deblauwe et al, 2006;Fragaszy et al, 2004;Sakura and Matsuzawa, 1991;Tonooka et al, 1997;Westergaard et al, 1995;Yocom and Boysen, 2010), but especially given the demonstrated prowess of wild chimpanzees in extensive and creative use of objects as tools in their environment. Why would captive chimpanzees not exhibit knowledge of physical support when such capabilities are both advantageous and necessary for their survival in the wild?…”
mentioning
confidence: 84%
“…2). 19,21,22,46,47 The largest known tool set comprises five tools used to get honey. 46 A specific order in the use of each tool of the set is needed to reach the goal.…”
Section: Digging Toolsmentioning
confidence: 99%
“…At La Belgique/Cameroon, termite puncturing sticks were manufactured from 8 plant species and fishing probes from 6 species [Deblauwe et al, 2006], while at Mt Assirik/Senegal, termite-fishing tools were provided by 6 species [McBeath and McGrew, 1982]. At Lossi Forest/Congo [Bermejo and Illera, 1999], perforating sticks are made from saplings of Euphorbiaceae, Acanthaceae, Marantaceae, Passifloraceae, Moraceae and Olacaceae.…”
Section: Tool Source Speciesmentioning
confidence: 99%